Assistência de enfermagem às urgências e emergências psiquiátricas no serviço de atendimento móvel de urgência em Mossoró-RN - Oliveira, Lucídio Clebeson de (2014)
This study aims to identify the concepts of professional nursing team on assistance in urgency and psychiatric emergencies in SAMU in Mossoró/RN, identifying the difficulties in implementing an emergency assistance to the user in psychiatric distress in this service and point strategies in pursuit of consolidation and expansion of comprehensive health care to the public. It is a descriptive research with qualitative and exploratory approach. The subjects were employees of the nursing staff of SAMU of that mentioned municipality. Semi-structured interviews are applied as tool for data collection. It was counted on the consent of the institution where the study was developed and approval by the Ethics Committee in Research of UFRN with CAAE No 17326513.0.0000.5537, besides signing the Informed Free Consent Term by the participants. Data analysis was done by means of thematic analysis proposed by Bardin. Thus , as a result of the research produced the following categories: mechanistic practice; dehumanization of care; need for qualification, barriers to assistance in urgency and psychiatric emergency and strategies in pursuit of comprehensive care, which proceeded in preparing two articles entitled "Nursing care to the emergency room and psychiatric emergencies in the mobile emergency care service" and "Barriers for emergency service and psychiatric emergencies in the mobile emergency care service". In the studied reality it was identified that nursing care offered to users in situations of urgency and psychiatric emergency is made based primarily on the use of chemical and physical restraints, as well as transportation to the general hospital, constantly using the police force support, which meets the guidelines of the Psychiatric Reform and thereby undermining the provision of an effective and humane care. This scenario is worsened by the lack of an organized network of services in mental health, where after the service the user is taken to a general hospital, considering that there is no ready or appropriate psychiatric emergency service as a Center of Psychosocial Care - CAPs III to reference it, thereby precluding the realization of a resolute and comprehensive care. Thus, it is concluded that nursing care is based on biologicist and medicine-centered model advocated by classical psychiatry, and that despite all the advances in psychiatric reform, still guides the mental health care, so the lack of service network organized in hierarchical and mental health, where the user in urgency and emergency service can be watched in full and the guidelines of the psychiatric reform can be realized in practice